Kajian Beberapa Tanaman Dataran Tinggi Koleksi Kebun Raya Cibodas dalam Kemampuan Penyerapan dan Konservasi Air - Masfiro Lailati (UIN Sunan Gunung Djati Bandung, 2021)
Mountainous ecosystems are very important areas in producing various environmental services, including as water catchment areas. Vegetation of tress plays an important role in maintaining the water balance in the soil. Heavy rainfall often causes problems in some of vulnerable areas. The study of several collection plants in the Cibodas Botanical Gardens – LIPI which has an altitude of 1,250 – 1,425 meters above sea level was tested to determine the ability to absorb the water and the process of transpiration through leaves. Ten (10) of woody plant species were selected by referring to the appearance of the large canopy trees, consisting of native and non-native plants. The measurement results showed that the Rasamala (Altingia excelsa Noronha) had the highest ability to absorb water at 27.38 × 10-6 ml/cm2/minute with the longest of transpiration through leaf i.e 56.1 ± 1.32 minutes and the lowest of chlorophyll content of 34.6. ± 0.74 SPAD. Meanwhile, Elaeocarpus griffithii (Wight) A. Gray has the lowest of the ability to absorb the water at 1.39 × 10-6 ml/cm2/minute. The fastest loss of water or transpiration through leaf occurred in Ficus variegata Blume 4.8 ± 0.25 minutes. Other plants showed varying results depending on their absorption capacity and leaf area.